SINTESIS BIOPELUMAS DARI MINYAK JELANTAH SEBAGAI ALTERNATIF PELUMAS RAMAH - Muchtar Arifin; Euis Kusniawati; Windi Amalia (Journal of Innovation Research and Knowledge, 2025)
Used cooking oil is a waste product from frying activities that poses a threat to the environment if not managed properly. This study aims to convert used cooking oil into environmentally friendly biolubricants through four main stages. The first stage involves activating zeolite catalysts using 6 M HCl solution to enhance their surface reactivity. This is followed by esterification and transesterification processes using 75% methanol to convert free fatty acids in the oil into methyl esters. The final stage is the synthesis of biolubricants by adding ethylene glycol to improve the lubricating properties of the final product. The best results were obtained at a reaction time of 60 minutes, producing biolubricants with a density of 0.854 g/ml, kinematic viscosity of 19.9 cSt, and a pour point of 2 °C. These values meet the quality standards for lubricants based on SNI 7182:2015, SNI 7069-10:2017, and SNI 06-7069.5-2005. This study demonstrates that used cooking oil can be transformed into a high-value, biodegradable product that is not only environmentally friendly but also a promising alternative to petroleum-based lubricants.